Tinjauan Teologis terhadap Kegerakan Bahtera - Flora Grace Pillay (Sabar : Jurnal Pendidikan Agama Kristen dan Katolik, 2025)
Heresy is a theological term that refers to teachings or doctrines that are rejected by church authorities because they are considered inconsistent with biblical truth. The term comes from the Greek word haíresis, which was originally neutral but has a negative connotation in the Christian context because it refers to deviations from official church teachings. Over time, heretics were seen as threats to church authority because they taught something different from the official interpretation entrusted to the church under the guidance of the Holy Spirit. The Ark Movement, as a contemporary example, shows how different interpretations can be considered heretical by church authorities. Although active in its ministry, this movement was accused of teaching doctrines that were inconsistent with biblical truth, as well as manipulating the Word of God to fulfill personal ambitions and interests. Therefore, it is important to conduct an in-depth theological study of these teachings that are considered heretical, to ensure harmony with biblical teachings and prevent doctrinal distortions that can damage the community of faith. Without a systematic effort to strengthen correct theological understanding, the risk of heresy and division within the community becomes greater.